Study of Quality of Life of People with HIV/AIDS (PWHA) based on Compliance with Taking Antiretroviral Drugs (ARV) - Khoirunnisa, Khoirunnisa; Afritayeni, Afritayeni; Rustam, Musfardi (Community Research of Epidemiology (CORE), 2021)
HIV/AIDS infection is a chronic disease that attacks the immune system which can be controlled by adherence to antiretroviral (ARV) drugs. The purpose of this study was to determine the relationship between adherence to taking ARV drugs and the quality of life of PWHA at the Limapuluh Public Health Center, Pekanbaru City. This type of quantitative analytic research with a cross sectional approach. The population is 125 people living with HIV who are outpatient at the Limapuluh Public Health Center Pekanbaru. The research sample is a minimum sample of 30 respondents and the sampling technique is accidental sampling using a questionnaire. Data analysis was univariate and bivariate. The results showed that the majority of adherence to ARV medication were 29 people (96.7%) and the majority of people living with HIV with very good quality of life were 28 people (93.3%). The results of the chi square test obtained a significant relationship between adherence to taking ARV drugs and the quality of life of PWHA p value = 0.000 0.05, then Ha is accepted. PWHA is expected to maintain adherence to ARV therapy as recommended by health workers in order to improve the quality of life of PWHA